2018
DOI: 10.3390/s18051588
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Estimation of Molded Plastic Plates Based on the Estimated Impulse Responses of Mechanoreceptive Units

Abstract: This study proposes a tactile estimation method of molded plastic plates based on human tactile perception characteristics. Plastic plates are often used in consumer products. The tactile evaluation plays an important role in product development. However, physical quantities not taking into account human tactile perception have been employed in previous tactile estimation procedures. Hence, in this study, we adopted the vibrational thresholds of the mechanoreceptive units—FA I, FA II, SA I and SA II—for stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Strain gauges are known for their versatility and accuracy and can be attached to many different surfaces due to being small and light [66]. Their low-cost nature allows for easier implementation in various tests and studies [42,43,[67][68][69]; however, humidity must be considered in prolonged usage as this can change the nominal resistance of the sensor. Payo et al, for example, made use of strain gauges in their study of microvibrations and its effects on slip detection.…”
Section: Strain Gaugementioning
confidence: 99%
“…Strain gauges are known for their versatility and accuracy and can be attached to many different surfaces due to being small and light [66]. Their low-cost nature allows for easier implementation in various tests and studies [42,43,[67][68][69]; however, humidity must be considered in prolonged usage as this can change the nominal resistance of the sensor. Payo et al, for example, made use of strain gauges in their study of microvibrations and its effects on slip detection.…”
Section: Strain Gaugementioning
confidence: 99%
“…To reproduce tactile sensations, technologies to quantify the tactile sensation of an object and to display tactile sensations using a tactile display are necessary. To quantify tactile sensation, it has been suggested that focusing on vibration information at the time of object touch is an effective approach given the human tactile perception mechanism [8], [9], [10], [11]. Tactile displays…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to extract meaningful information from vibration data obtained by tracing a simple vibration sensor on an object [16][17][18][19][20][21][22]. Because the four types of mechanoreceptors in our body have different frequency characteristics [23][24][25], they work as lters for vibration stimulations on the skin.…”
Section: Introductionmentioning
confidence: 99%